Mekanisme Pasar dalam Perspektif Studi Islam - Isnaeni Deviyanti; Meylisa Hayati Putri; Raihani Aqila Ghinarahma (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study examines the market mechanism from the perspective of Islamic economics as a response to conventional economic systems that tend to emphasize either free-market principles or full government intervention. In Islam, the market mechanism is governed by principles of justice, transparency, and balance among the interests of individuals, the state, and society. This research highlights the thoughts of classical Islamic scholars such as Abu Yusuf, Ibn Taymiyyah, Al-Ghazali, and Ibn Khaldun, who had already elaborated on the concepts of markets, pricing, supply and demand, and ethical conduct in transactions long before Western economists developed similar ideas. Using a qualitative approach and literature review, this article analyzes various market distortions such as ihtikar (hoarding), tadlis (fraud), riba (usury), and gharar (uncertainty), as well as the role of government in limited intervention to maintain balance and fairness. The findings show that the Islamic market mechanism is not solely focused on economic efficiency, but is also deeply rooted in moral and spiritual values.